Radiographic Evaluation and Comparison of Plate Fixation after Triple Pelvic Osteotomy in 32 Dogs with Hip Dysplasia - Koch, D. A.; Hazewinkel, H. A. W.; Nap, R.C.; Meij, B.P.; Wolvekamp, W. Th. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Triple pelvic osteotomy (TPO), as a treatment for canine hip dysplasia, was evaluated radiographically in 38 cases. Several parameters on radio-graphs of the pelvis, taken pre- and postoperatively, as well as six weeks and three months after the operation, were measured and compared. The results were also compared between iliac osteotomy fixation with the canine pelvic osteotomy plate (CPOP, n = 16) and the twisted dynamic compression plate (DCP, n = 22). Acetabular support (from 0.21 to 0.89), Norberg angle (from 77.6° to 111.8°) and hip joint congruence improved significantly after TPO. Dorsal pelvic width did not change, whereas, due to rotation, ventral pelvic width decreased to 80% of its pre-operative value. Osteophyte formation was judged to be moderate three months after the operation. Comparison of the two plating methods showed significant postoperative advantages for the CPO P group in terms of a higher Norberg angle and a better congruence. There was some loosening of 33% of the screws in both groups, but this did not interfere with the aim of the TP O procedure.The effect of triple pelvic osteotomy, as a treatment for canine hip dysplasia, was investigated retrospectively by means of radiographs. Acetabular support, the Norberg angle, and hip joint congruence improved significantly after the operation. Iliac osteotomy fixation, with the canine pelvic osteotomy plate, displayed advantages over the twisted dynamic compression plate. Screw loosening occurred frequently but without any major consequences.
Keywords: Hip dysplasia; triple pelvic osteotomy; radiology